Pengaruh manajemen risiko terhadap pengambilan keputusan investasi pada perusahaan manufaktur - umam, reza khoirul (Maliki Interdisciplinary Journal, 2025)
This study aims to evaluate the impact of risk management on investment decisions in manufacturing companies. In the context of globalization and increasingly tight business competition, manufacturing companies face various challenges in making the right investment decisions. Risk management plays an important role in helping companies identify, evaluate, and manage various risks that can affect the achievement of their business goals. This study applies a quantitative approach with samples from manufacturing companies to test the hypothesis regarding the impact of risk management on the quality of investment decisions. The findings of this study indicate that the implementation of risk management in manufacturing companies is at a moderate to good level, covering four main aspects: risk identification, risk evaluation, risk mitigation, and monitoring and evaluation. The investment decision-making process is carried out in a structured manner. Companies that implement a good risk management system tend to make better quality investment decisions based on the right information. This study provides a practical contribution for manufacturing companies to improve their risk management system and integrate it into the investment decision-making process.